EFFECTS OF FEEDING FREQUENCY ON THE GROWTH AND SURVIVAL OF CATFISH (CLARIAS MACROCEPHALUS GUNTHER) LARVAE - Mollah, M F A; Tan, E S P (Indian Journal of Fisheries, 2011)
Studies on the effects of feeding frequency on the growth and survival with5-day old catfish [Clarias macrocephalus, Gunither) larvae of initial size rangingfrom 7.9 + 0.4 mm to 8.0 + 0.4 mm in total length were conducted in glassaquaria over a period of 28 days at an initial stocking density of 4 fish 1" . Fourfeeding frequencies in the order of five feedings, three feedings, two feedings andone feeding day " wiiitb live food {Moina and/or Tubifex worms) were studied.Results indicated that a feeding frequency of three times day" was as good asthat of five times when the growth of larvae in term of length-gain was compared.Larvae under the feeding frequency of five and three times day' showed significantly(p < 0.05) higher growth and survival than those at two feedings andone feeding day" , The survival rate did not differ significantly at the feedingfrequency of five and three times day" . A feeding frequency of three times daywith live food was, therefore, appeared to be suitable for rearing catfish larvae atthe ambient temperature which ranged between 26 and 31Â°C.